2017
DOI: 10.15407/ubj89.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Corvitin restores metallothionein and glial fibrillary acidic protein levels in rat brain affected by pituitrin-izadrin

Abstract: In this research, we investigated the effect of pituitrin-izadrin induced injury on the levels of metallothionein (MT) and soluble and filament forms of glial fibrillary acidic protein (GFAP) in the hippocampusA strocytes are amongst the earliest and prominent to express changes under attacks [1]. They are the most numerous nonneuronal cell types in the central nervous system (CNS) and make up about 50% of the volume of the human brain [1,2]. Their functions are known to be critical, such as scavenge transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In our previous studies, an established regulatory action of Corvitin on the metallothionein (MT) and glial fibrillary acidic protein (GFAP) levels in various parts of the brain was shown. It is known that GFAP is responsible for the functional activity of astrocytes and nutrition of neurons, while MT regulates gene expression and cell adaptation to the stress factors [ 60 ]. Behavioral activation of rats with PIMD after the treatment by 2-OG is the definitive result of its multifactor impact on brain metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, an established regulatory action of Corvitin on the metallothionein (MT) and glial fibrillary acidic protein (GFAP) levels in various parts of the brain was shown. It is known that GFAP is responsible for the functional activity of astrocytes and nutrition of neurons, while MT regulates gene expression and cell adaptation to the stress factors [ 60 ]. Behavioral activation of rats with PIMD after the treatment by 2-OG is the definitive result of its multifactor impact on brain metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, oxidative stress can interact with individual signalling pathways, which may be more closely related to the detrimental effect and specificity of outer stimuli. In the nervous system, for example, the glial fibrillary acidic protein (GFAP) is known as a neurotoxicity biomarker (Shiyntum et al, 2017;Abdel Salam, 2021) which is obviously connected with the ROS production (Gasso et al, 2020a;Fernandes & Özcelik, 2021). On the other hand, the inflammation is an important part of innate defence against infectious agents as well as xenobiotic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…After 7 days of the experiment, a decrease in GFAP in frog brain astrocytes was observed, which might indicate impaired astrocyte development (Flaskos, 2014). Given that GFAP is a classical biomarker of astrocyte disorders (Eliasson et al, 1999;Tykhomyrov et al, 2016;Shiyntum et al, 2017), a decrease in GFAP levels may indicate a dysfunction of brain nervous tissue (Müller et al, 2012). According to Markiewicz et al (2006), a decrease in GFAP was observed in the brain of rats after administration of low doses of the pyrethroid cypermethrin after 2 and 21 days of the experiment.…”
Section: Discussionmentioning
confidence: 99%